Nephroprotective Effects of Polyherbal Formulation on Gentamicin-induced Toxicity in Wistar Rats - Aswar, Anand P.; Hajare, Sunil W.; Ingole, Ranjit S.; Ingawale, Maheshkumar V.; Kuralkar, Prajakta S.; Waghmare, Sunil P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Effect of a polyherbal formulation (polyherbal alcoholic extract; PAE) prepared from Withania somnifera (root), Aegle marmelos (leaves), Tribulus terrestris (fruit) was studied on gentamicin-induced nephrotoxicity. Thirty Wistar rats were equally divided into five groups; group I (control), group II (gentamicin alone), group III (prophylactic), group IV (curative) and group V (formulation alone). Gentamicin caused signs of depression, dullness, polyurea, restlessness, reduced body weight, and reduced water and feed intake. These toxicity signs were recovered in the PAE pre-treated prophylactic group; however, in the PAE-treated therapeutic group, some mild toxicity signs were noticed and subsided gradually. Gentamicin increased relative kidney weight but in groups III and IV animals, no significant effect was observed. The Hb, PCV, TEC, TLC and MCV of group II animals revealed a significant decrease, whereas; BUN, creatinine, AST, ALT, ALP, total protein, albumin and globulin were significantly increased. The PAE treatment caused significant recovery in these hematobiochemical parameters in groups III and IV. Gentamicin caused histopathological alterations in kidney represented by focal renal degenerative and necrotic changes, with intratubular hyaline cast. In PAE-treated groups III and IV, minimal histopathological alterations were seen. In conclusion, PAE showed significant protective and moderate therapeutic potential against gentamicin-induced nephrotoxicity in Wistar rats.
Keywords: Gentamicin; Nephrotoxicity,; PAE,; Wistar rats; Withania